A cobalt‐based metal–organic framework for efficient separation of propene from propane via electrostatic effect. Issue 8 (29th April 2022) - Chen, Yongwei; Tu, Shi; Fu, Peng; Wu, Houxiao; Wang, Xingjie; Wu, Ying; Li, Zhibo; Xia, Qibin
Abstract: Exploring porous materials for efficient adsorption separation of propene/propane (C3 H6 /C3 H8 ) mixture to replace the energy‐intensive cryogenic distillation remains a daunting challenge due to the similar physiochemical properties of the two gases. Herein, we report a cobalt‐based metal–organic framework, MUF‐17, for efficient separation of C3 H6 /C3 H8 by exploiting the electrostatic effect. MUF‐17 exhibits a moderate C3 H6 uptake of 2.44 mmol/g and good C3 H6 /C3 H8 selectivity of 3.8 at 298 K and 1.0 bar. Breakthrough experiments confirm the excellent C3 H6 /C3 H8 separation with the C3 H6 captured productivity of 1.26 mmol/g. Molecular simulations reveal that MUF‐17 enables effective trapping of C3 H6 and discrimination from C3 H8, due to the electrostatic potential compatibility well fitting for C3 H6 within the confined pore space that provides the stronger binding sites of C3 H6 than C3 H8 . Furthermore, other combinational features of moisture stable, low‐cost, ready large‐scale synthesis, and good recyclability are observed for MUF‐17, making it a promising candidate for C3 H6 /C3 H8 separation.